2022
DOI: 10.3389/fimmu.2022.790400
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Updated Diagnostic Criteria for Paraneoplastic Neurologic Syndromes in China

Abstract: BackgroundRecently, the paraneoplastic neurologic syndrome (PNS) diagnostic criteria have received a major update with a new score system over the past 16 years. We aimed to evaluate the diagnostic performance and clinical utility in China.MethodsAn eligible cohort of 113 Chinese patients diagnosed with PNSs from the Second Affiliated Hospital School of Medicine Zhejiang University and published data were enrolled retrospectively. Data including clinical phenotype, antibody type, the presence of cancer, and du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
(23 reference statements)
1
4
0
Order By: Relevance
“…The findings of our cohort align with the recent literature, including the study by Cai et al, 2022, that provides insight into the clinical application of the two different sets of diagnostic criteria [34]. Accordingly, it should be highlighted that although the 2021 PNS-Care criteria are characterized by higher specificity compared to the 2004 criteria, they are also characterized by a lower sensitivity [3,5].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The findings of our cohort align with the recent literature, including the study by Cai et al, 2022, that provides insight into the clinical application of the two different sets of diagnostic criteria [34]. Accordingly, it should be highlighted that although the 2021 PNS-Care criteria are characterized by higher specificity compared to the 2004 criteria, they are also characterized by a lower sensitivity [3,5].…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, the lower diagnostic sensitivity of the revised 2021 PNS-Care criteria based on currently available evidence may also have detrimental effects, increasing the risk of under-or misdiagnosis (i.e., misclassification as probable/possible PNS) or causing significant delays in treatment initiation [5]. In view of the prognostic implications and in line with the previous literature, the long-term follow-up and monitoring of patients with probable/possible PNS is warranted to establish causal associations between detected Abs and underlying tumors [5,34]. We recommend weighing the harms and benefits of early vs. delayed treatment initiation in cases of probable/possible PNS on a per patient basis.…”
Section: Discussionmentioning
confidence: 99%
“…5, Table 3 ), the criteria for probable and definite AE have been externally validated and show good concordance 4 , 24 . Moreover, for the diagnosis of PNS, updated criteria for PNS and the PNS-care score show improved specificity when compared to criteria published in 2004 25 , 26 . Therefore, with exceptions for brainstem encephalitis 4 VGKC, IGLON-5, CASPR2, LGI-1 and rarely Ri antibody-mediated PNS known for their indolent clinical course and/or lack of neuroinflammatory features in the CSF 27 31 , most immune mediated neurological syndromes have neuroinflammatory findings in CSF studies or neuroimaging and are mandatory findings in the criteria of AE to establish the diagnosis.…”
Section: Discussionmentioning
confidence: 90%
“…Finally, the PNS-Care panel updated the diagnostic criteria for PNS on the basis of new phenotypes and antibodies [ 4 ], but the research revealed that the new PNS-Care Score provides a specific and strict approach to improving diagnostic accuracy. However, its increased risk of underdiagnosis is a cause for concern [ 26 ]. Some of the patients in our cohort were not tested for antibodies, as we used the 2004 diagnostic criteria [ 13 ].…”
Section: Discussionmentioning
confidence: 99%